Hello! I'm having a pretty big problem intersecting parametric lines. I'm using the equations: x = x1 + t(x2 - x1) y = y1 + t(y2 - y1) Given the 2 lines: x = x1 + t(x2 - x1) y = y1 + t(y2 - y1) x = x3 + t(x4 - x3) y = y3 + t(y4 - y3) I calculate the intersection, using this: t = ( x3 - x1 ) / ( (x2 - x1) - (x4 - x3) ) And then I would plug it into the first line... For some odd reason...it doesn't work! And the funny thing is, that it used to work in my program. I'm not sure if I made any changes, but it's really screwing things up... Please help! P.